Reinforcement Learning: Past, Present, and Future Perspectives - Hofmann, Katja (Thirty-third Conference on Neural Information Processing Systems (NeurIPS), 2019)
Reinforcement learning (RL) is a systematic approach to learning and decision making. Developed and studied for decades, recent combinations of RL with modern deep learning have led to impressive demonstrations of the capabilities of today's RL systems, and have fueled an explosion of interest and research activity. Join this tutorial to learn about the foundations of RL - elegant ideas that give rise to agents that can learn extremely complex behaviors in a wide range of settings. Broadening out, I give a (subjective) overview of where we currently are in terms of what's possible. I conclude with an outlook on key opportunities - both for future research and for real-world applications of RL.
Tutorial